Transurethral resection of prostate just following high intensity focused ultrasound in localized prostate cancer--trial for early removal of the urethral catheter - Otsuki, Hideo (Hinyokika kiyo. Acta urologica Japonica, 2008)
We studied the impact of combined transurethral resection of the prostate (TURP) and high intensity focused ultrasound (HIFU) for localized prostate cancer (CaP) to decrease side effects such as prolonged urinary voiding disturbance observed after HIFU treatment. Included in this study were 18 patients with clinically localized CaP indicated for HIFU just followed by TURP (TUR combination group). Complete response was defined in accordance with ASTRO consensus statement and negative sample in biopsies performed 6 months after the HIFU treatment. Prostate specific antigen (PSA) nadir, International Prostate Symptom Score (IPSS) and morbidity during follow-up of TUR combination group were compared with those of a control of 18 patients who took HIFU treatment alone (HIFU monotherapy group). No statistical significances on the values of preoperative parameters (PSA, prostate volume, Gleason score, and IPSS) between these two groups. The median follow-up duration was 10 (5-15) months in both groups. A statistically significant impact was observed between TUR combination group and HIFU monotherapy group on median catheter time (5 versus 13 days, P<0.0001), PSA nadir (0.096 ng/ml versus 0.430 ng/ml in median, P<0.05) and the evolution of the post-treatment IPSS (8 versus 13.5 in median, P<0.0003) at 3 months after treatment. Urethral stricture necessary for urethral dilation was noted in 1 patient (5.6%) in the TUR combination group while in 2 (11.1%) in the HIFU monotherapy group. CR was obtained in 88.9% in the TUR combination group and 83.3% in the HIFU monotherapy group. Our study suggests that the combination of TURP with HIFU treatment improves posttreatment urinary status without additional morbidity